BANK SPECIFIC FACTORS AFFECTING THE EFFICIENCY OF REGIONAL DEVELOPMENT BANKS - Anneke Puspasari; D S Priyarsono; Hendro Sasongko (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2020)
Regional Development Banks (RDB) are part of the banking industry which has an important role in regional development. Therefore, RDB performance is important to be evaluated, and efficiency is an important indicator in measuring performance. The purpose of this study is to analyze the efficiency of the Regional Development Bank (RDB) in Indonesia and the internal factors that influence efficiency. Based on data of 26 RDBs in the study from 2011Q1 to 2019Q4, this study uses Data Envelopment Analysis (DEA), and the Tobit regression to investigate the determinants of technical efficiency. This analysis aims to explain the variations in calculated efficiencies to a set of internal explanatory variables. The results showed that most RDBs were technically inefficient during the study period. Furthermore, the internal variables that affect are size, capital adequacy ratio (CAR), loan to deposit ratio (LDR), return on asset (ROA), Listed Bank.